Rol del profesional médico en la prevención y atención de casos de violencia de género en el ecuador - Guzmán Herrera, Gisella Liliana (Machala : Universidad Técnica de Machala, 2020)
INTRODUCTION: Today gender violence is a common problem in society; Due to the fact that it is covered up by housewives and health professionals who prefer to ignore their obligations, increasing the figures of abuse against women in the country. Around 70% of women suffer from violence in the world and one in six women in Ecuador have reported being abused; demonstrating the urgent need to describe and define the actions of medical personnel to combat this disease by improving the quality of life in the community. OBJECTIVE: To determine the role of the Medical professional and the Health Team of the first level of care in patients who are victims of gender violence in Ecuador. MATERIALS AND METHODS: An abductive bibliographic review is applied; by compiling, analyzing and interpreting information from scientific societies such as Scielo, Taylor and Francis, Dialnet and indexed in Latindex and Scimago by verifying that they comply with the relevant academic rigor. CONCLUSION: In patients who are victims of gender violence, the role of the doctor is to coordinate the treatment and follow-up of the case; the role of the nurse to diagnose and identify the case of gender violence; the role of the psychologist is to provide emotional support and the social worker must organize visits and manage actions with the respective authorities when solving the case holistically.
INTRODUCCIÓN: Hoy en día la violencia de género es un problema común en la sociedad; debido a que es encubierto por las amas de casa y profesionales de la salud que prefieren hacer omisión de sus obligaciones incrementando las cifras de abusos contra mujeres en el país. Alrededor del 70% de las mujeres sufren de violencia en el mundo y una de cada seis féminas en el Ecuador han reportado ser abusadas; demostrando la necesidad imperiosa de describir y definir el accionar del personal médico para combatir este mal mejorando la calidad de vida en la comunidad. OBJETIVO: Determinar el rol del profesional Médico y del Equipo de Salud del primer nivel de atención en pacientes víctimas de violencia de género en Ecuador. MATERIALES Y MÉTODOS: Se aplica una revisión bibliográfica de carácter abductivo; al compilar, analizar e interpretar información de sociedades científicas como Scielo, Taylor and Francis, Dialnet e indexadas en Latindex y Scimago al verificar que cumplan con el rigor académico pertinente. CONCLUSIÓN: En pacientes víctimas de violencia de género, el rol del médico es de coordinar el tratamiento y seguimiento del caso; el rol de la enfermera diagnosticar e identificar el caso de violencia de género; la función del psicólogo es brindar apoyo emocional y el trabajador social debe organizar las visitas y gestionar el accionar con las autoridades respectivas al solucionar el caso en forma holística
Keywords: VIOLENCIA DE GENERO; PROFESIONALES DE LA SALUD; ATENCION PRIMARIA; SISTEMA DE SALUD